Aneurysm in the anterior inferior cerebellar artery-posterior inferior cerebellar artery variant: Case report and review of literature. (2016) - Akhtar, Saad; Azeem, Abdul; Jiwani, Amyna; Javed, Gohar
Highlights: We reported a case of an aneurysm in the AICA-PICA variant which was subsequently excised. Considerable variation exists in the anatomy of the vertebrobasilar system. Understanding the variations and the aneurysms that may arise from them is an important aspect of neurosurgical practice. Abstract: Introduction: There are variations in the anatomy of the vertebrobasilar system amongst which the Anterior Inferior Cerebellar Artery-Posterior Inferior Cerebellar Artery (AICA-PICA) variant is thought to have a prevalence of 20–24% (based on retrospective studies). Despite this, aneurysms of the AICA-PICA variant are rare. We present a case of an AICA-PICA aneurysm and discuss its presentation and management, along with a review of literature. Presentation of case: We describe the case of a 35 year old female who presented with signs of meningismus. On the basis of radiological imaging it was initially misdiagnosed as a thrombosed arteriovenous malformation (AVM). The patient was eventually discharged with a plan of interval imaging and interventional radiology (if required). The patient presented again with similar signs and symptoms. Re-evaluation of imaging revealed an aneurysm of the AICA-PICA variant which was managed surgically. Discussion: Aneurysms of the AICA-PICA variant are rare. The radiological features and surgical management represent a unique clinical entity and are discussed below. Conclusion: The prevalence of the AICA-PICA variant might be high but aneurysms in this vessel are rare. The scant knowledge available on this subject makes it a diagnostic difficulty.